Environmental Governance as a Model of Environmental Management - Budi Kristianto (Journal of Wetlands Environmental Management, 2014)
The concept of environmental governance does not promise practical solutions and provides short guidance in solving intertwined environmental problems in Indonesia. But at least environmental concept is useful when we try to realize environmental management in Indonesia currently. The worst is that the mistake has become routine manifesting in pragmatism in environmental management. Before it all too late, it is better that we keep in mind a German proverb in the beginning of this writing, which more or less, means â€œ we do not know what the future brings, but we know that we should act.â€